Poverty by social, religious and economic groups in India and its largest states 1993-1994 to 2011-2012 - Arvind Panagariya and Vishal More (Indian Growth and Development Review, 2014)
Purpose – The purpose of this paper is to ground in serious empirical evidence the debate on whether the post-reform acceleration in growth has helped bring poverty down for all economic, social and religious groups and in all state or has left certain groups or states. Design/methodology/approach – The paper uses unit-level data from the so-called thick rounds of expenditure surveys by National Sample Survey (NSS) in the years 1993-1994, 2004-2005, 2009-2010 and 2011-2012 and estimates the proportion of the population below the official Tendulkar line. Adequate care is taken to address the issue of sample size in reporting the estimates. Findings – Whether we slice the data by social, religious or economic groups, by states or by rural and urban areas, poverty has significantly declined between 1993-1994 and 2011-2012 with a substantial acceleration during the faster-growth period from 2004-2005 to 2011-2012. Poverty rates among the disadvantaged social groups and minorities have declined faster so that the gap in poverty rates between them and the general population has declined. In 7 of the 16 states with large Muslim populations, the poverty rate for them is now below that for the Hindus. Research limitations/implications – Use of survey data has its limitations, especially when the sample sizes are small. The paper also does not assess the direct contribution of growth in relation to that through redistribution. Practical implications – The paper presents implications for identification of the poor for the purpose of designing targeted interventions. Originality/value – This is the first paper to offer up-to-date estimates of poverty by social, religious and economic groups, by states and by rural and urban areas.